Sharia-Based Digital Pedagogical Transformation: A Strategy to Accelerate Teacher Professionalism in the Digital Learning Ecosystem - Sony Kuswandi; Rusdi Bin Jamaludin (Attractive : Innovative Education Journal, 2025)
The dynamics of the disruptive era require madrasas to reorient their pedagogy through the utilization of digital ecosystems without neglecting religious identity. This study aims to analyze strategies for accelerating teacher professionalism within the framework of Sharia-based Digital Pedagogical Transformation at Madrasah Aliyah Al Muhajirin Purwakarta. The method used was a qualitative descriptive case study, where data were collected through in-depth interviews, participatory observation, and documentation studies of leaders and teaching staff. Data analysis was carried out interactively, including data reduction, presentation, and drawing conclusions with validity testing through source triangulation. The results show that the digital pedagogical transformation at MA Al Muhajirin was successfully accelerated through the internalization of Sharia values ​​that position technological mastery as intellectual jihad and digital ethics as a manifestation of muraqabah. The implemented managerial strategy integrates digital literacy policies into the Islamic boarding school culture, thus creating an innovative, transparent, and accountable learning ecosystem. Educators not only experienced increased technical skills but also strengthened moral integrity in managing interactions in cyberspace. The implications of this research offer a Digital-Syar'i transformation model as a strategic reference for Islamic educational institutions in modernizing teacher governance that is adaptive yet rooted in moral excellence. The success of this model confirms that spiritual values ​​can be a primary catalyst for accelerating teacher professionalism in the digital era